Take the 2-minute tour ×
MathOverflow is a question and answer site for professional mathematicians. It's 100% free, no registration required.

Let us consider a sequence $(p_l)_l$ of polynomials on $[0,1]$ that converge uniformely, as $l\to \infty$, to a function $f$ defined on $[0,1]$.
I denote the polynomials $p_l(t) = \sum_{k=0}^{m(l)} a_k(l) t^k$.
I have also a certain quantity $\lambda(p_l) \in \mathbb{R}$ which has the following asymptotic behaviour :

$\lambda(p_l)(x) = \sum_{k=0}^{m(l)} a_k(l)\tfrac{1}{1+k/x} \underset{x\to\infty}{\sim} \sum_{k=0}^{m(l)} a_k(l) \sum_{j=0}^{\infty}(-1)^j (\tfrac{k}{x})^j$.
So:

$\lambda(p_l)(x) \underset{x\to\infty}{\sim} \sum_{k=0}^{m_l}a_k(l) - \sum_{k=0}^{m(l)} a_k(l)\tfrac{k}{x} + ... = p_l(1) - \tfrac{p_l'(1)}{x} + ...$

Naively, I want to apply the limit to obtain:
$\lambda(p_l)(x) \underset{x\to\infty}{\sim} f(1) - \tfrac{f'(1)}{x} + ...$
Questions : Do I have first check some hypothesis to write it? Do you have any reference about applying the limit in an asymptotic behavour?
Thank you a lot.

share|improve this question
    
You can't expect $\lambda(p_\ell)(x) \underset{x\to\infty}{\sim} f(1) - \tfrac{f'(1)}{x} + ...$ for all $\ell$, because $p_\ell$ for fixed $\ell$ is just an arbitrary polynomial. You must have some limit as $\ell \to \infty$ in mind. –  Robert Israel Jan 21 '13 at 15:23
    
$p_\ell(1) \to f(1)$ by your convergence assumption, but ${p_\ell}'(1)$ can be much different from $f'(1)$. In fact the uniform limit of polynomials on $[0,1]$ need not be differentiable at all. –  Robert Israel Jan 21 '13 at 15:28
    
Of course, I had $l\to \infty$ in mind. For your second remark, what if I assume f smooth around 1? Don't the derivatives of $p_l$ converge to the derivatives of $f$ at 1, as $l\to \infty$? –  pilipilax Jan 21 '13 at 15:38
    
No they don't. For example, if $p_j(x) = T_j(x)/j$ where $T_j$ is the $j$'th Chebyshev polynomial of the first kind, $p_j \to 0$ uniformly on $[-1,1]$ but $p_j'(1) = j$. –  Robert Israel Jan 21 '13 at 19:19
    
Here is the reasonning that maybe makes me misunderstand: Let $a\in [0,1]$ on which every $p_l$ and $f$ are differentiable. In $\tfrac{p_l(x)-p_l(a)}{x-a}=\tfrac{p_l(x)-f(a)}{x-a} + \tfrac{f(a)-p_l(a)}{x-a}$, the first term tends to $\tfrac{f(x)-f(a)}{x-a}$ and the second to $0$ as $l\to\infty$. So when $x\to a$, we have the equality of derivatives. Am I wrong? –  pilipilax Jan 22 '13 at 10:23

1 Answer 1

Note that the quantity $\lambda p$ depending on the parameter $x$, as you define it for polynomials $p(t):=\sum_{k=0}^m a_k t^k$, that is $$(\lambda p )(x)=\sum_{k=0}^m a_k \frac{1}{1+k/x}\, , $$ can be extended to a positive, bounded linear operator $$\lambda :C^0([0,1])\to C^0_b([0,\infty))$$ taking the function $f\in C^0(I)$ to
$$(\lambda f)(x):=\int_0^1 xt^{x-1}f(t)dt\, .$$ In particular, $(\lambda f)(x)=f(1)+o(1)$ as $x\to+\infty$. For $f\in C^1([0,1])$ we also have, integrating by parts $$(\lambda f)(x)=f(1)-\int_0^1 t^x f'(t)dt=f(1)-f'(1)/x+o(x^{-1}),\qquad (\mathrm{as}\, x\to+\infty) \, .$$

$$*$$

You can also write, changing variable in the integral, ($t=e^{-\tau}$) $$(\lambda f)(x):=x \int_0^{+\infty} e^{-\tau x}f(e^{-\tau})d\tau\, .$$
Thus your $\lambda f$ is the Laplace transform of $f(e^{-\tau})$, times $x$. Thus you can profit of the asymptotic theory for Laplace transform of functions, developed in most textbooks on the subject.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.